2020
DOI: 10.1002/acr.23999
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Dose Methotrexate and Mucocutaneous Adverse Events: Results of a Systematic Literature Review and Meta‐Analysis of Randomized Controlled Trials

Abstract: Objective. Methotrexate (MTX) increases the risk of alopecia and stomatitis, but the prevalence of these adverse events among rheumatic patients taking MTX is poorly defined. We conducted a systematic literature review and meta-analysis to estimate the prevalence of alopecia and stomatitis with MTX in rheumatic diseases.Methods. We searched PubMed, The Cochrane Library, and CINAHL databases for double-blind randomized controlled trials (RCTs) with an MTX monotherapy arm. Alopecia, stomatitis, and oral/mouth ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
(16 reference statements)
0
3
0
3
Order By: Relevance
“…Mazaud and Fardet 21 pooled data of clinical trials investigating MTX with or without cointervention, and they found that 9.7 % of patients, from 30 studies, developed oral ulcers. Lalani et al 22 pooled data of RCTs investigating monotherapy MTX for RA, and they reported 8% of patients, from 21 studies, developed oral ulcers. In their narrative review, Kalantzis et al 4 reported 14% by pooling the data from 18 studies.…”
Section: Discussionmentioning
confidence: 99%
“…Mazaud and Fardet 21 pooled data of clinical trials investigating MTX with or without cointervention, and they found that 9.7 % of patients, from 30 studies, developed oral ulcers. Lalani et al 22 pooled data of RCTs investigating monotherapy MTX for RA, and they reported 8% of patients, from 21 studies, developed oral ulcers. In their narrative review, Kalantzis et al 4 reported 14% by pooling the data from 18 studies.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal upset, fatigue, hair loss, and oral ulcers are commonly reported adverse effects but may be mitigated by subcutaneous administration, or higher doses of prophylactic folic acid, respectively. Lalani et al recently demonstrated with a meta-analysis relatively low prevalence of stomatitis and alopecia (between 5.7 and 8.0% and between 1.0 and 4.9%, respectively) in patients taking methotrexate [ 122 ]. Bone marrow suppression and hepatotoxicity may occur, and routine lab monitoring is required while on therapy to ensure patient safety [ 6 ].…”
Section: Treatmentmentioning
confidence: 99%
“…В ряде источников показано, что возникновение НР в полости рта зависит от получаемой дозы МТ незначительно [7,13,14]. Предположительно, это может объясняться секрецией препарата со слюной, повышением его концентрации в ротовой жидкости и развитием местного токсического эффекта даже при использовании минимальных дозировок [11].…”
Section: патогенез нежелательных реакцийunclassified
“…В некоторых исследованиях было показано, что поражения СОПР являлись наиболее частым побочным эффектом при применении низких доз МТ [11]. По данным различных исследований, частота развития стоматита при монотерапии низкими дозами МТ колебалась от 5,7 до 17,0% [10,[13][14][15], в одном исследованиидостигала 60,7% [16]. Такое существенное различие может быть обусловлено разными схемами терапии, сопутствующим приемом фолиевой кислоты.…”
Section: клинические варианты нежелательных реакций в полости ртаunclassified
See 1 more Smart Citation